Avaliação da termoterapia na qualidade fisiológica e sanitária em sementes de pinhão-manso armazenadas - Schneider, Cristina Fernanda (2012)
Among the many species that can be used to obtain vegetable oil for energy, Jatropha is considered one of the best agricultural options. Therefore, it is necessary to have seeds with good physiological and health quality in order to have a good establishment of plants in the field. This study aimed to evaluate the efficiency of heat treatment to the control of seed-borne pathogen in stored Jatropha seeds. The seeds of Jatropha were collected in Dourados MS, and were subjected to processing and sun drying, and then conducted to the storage in a dry chamber in glass packing with a screw cap and a capacity of 500 mL, for periods of 0, 90, 180, 270 and 360 days. After each storage period, seeds were subjected to thermotherapy by immersion in hot water at temperatures of 45 °C, 50 °C and 55 °C for 15 minutes; the control treatment was immersed in water at room temperature (25±2 °C) for 15 minutes. The parameters evaluated were: moisture content, weight of thousand seeds, health, germinations, emergence rate index and electrical conductivity. The experimental design was completely randomized with a factorial 5x4. For data analysis it was found that heat treatment at temperatures of 45 °C, 50 °C and 55 °C did not affect germination and the cell membrane integrity of the seed. In seeds stored after 180 days the use of thermotherapy contributed to the conservation of seed vigor. The fungus Penicillium sp. and Acremonium sp. were eliminated by thermotherapy at temperatures of 45° C, 50° C and 55° C, and Aspergillus sp. was controlled at a temperature of 55° C in periods of storage of 180 and 270 days.